Dampak Pembangunan Ekonomi dan Keterbukaan Terhadap Pertumbuhan Kota di Indonesia Tahun 1970-2002 - Asih Sriwinarti (Universitas Islam Indonesia, 2005)
This study uses Error Correction Model to test the relationship between urban growth (primacy) and size of country, economic development, density, industrialization and openness. We find that size of country (GDP) and density has less primacy in long term. The results are consistent with expectations from simple economic models of urban structure. In long term, primacy increases with economic development (GDPC), industrialization and openness.Keywords: primacy, economic development, openness, Error Correction Model